2019
DOI: 10.3389/fpubh.2019.00079
|View full text |Cite
|
Sign up to set email alerts
|

Public Involvement in Global Genomics Research: A Scoping Review

Abstract: Public involvement in research occurs when the public, patients, or research participants are actively contributing to the research process. Public involvement has been acknowledged as a key priority for prominent human genomics research initiatives in many different countries. However, to date, there has been no detailed analysis or review of the features, methods, and impacts of public involvement occurring in human genomics research projects worldwide. Here, we review the reported public involvement in 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(122 citation statements)
references
References 40 publications
(60 reference statements)
0
122
0
Order By: Relevance
“…Additionally, there are identified gaps in the literature on reporting methods and the extent of public involvement in clinical trials which constitute a critical share of health and biomedical research design. A study of public research involvement in online trials concerning health selfmanagement, for example, found that detailed reporting of such involvement was hindered by role confusion between research volunteers and trial participants [22]. Other related study findings contribute to the literature by documenting researchers' perspectives and experiences about sharing results with research participants.…”
Section: Challenges and Limitationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, there are identified gaps in the literature on reporting methods and the extent of public involvement in clinical trials which constitute a critical share of health and biomedical research design. A study of public research involvement in online trials concerning health selfmanagement, for example, found that detailed reporting of such involvement was hindered by role confusion between research volunteers and trial participants [22]. Other related study findings contribute to the literature by documenting researchers' perspectives and experiences about sharing results with research participants.…”
Section: Challenges and Limitationsmentioning
confidence: 79%
“…Health and biomedical citizen science is not readily defined as a separate practice or associated with a specific framework or schema, although the field is increasingly identified with a number of engagement models [21][22][23][24]. Projects involving human health and participants can be viewed as citizen science among various forms of community-based participatory research, action research, patient and public involvement (PPI), self-quantification, crowdsourced health research, among other practices [15,[23][24][25][26].…”
Section: Citizen Science Models Of Participatory Health Researchmentioning
confidence: 99%
“…Public involvement aims to have the public, patients or research participants actively contributing to the research process. 6 Public involvement is seen as a means to produce and maintain public trust and legitimacy, which are essential for the functioning of biobanks. 6 This increase in efforts to involve the public in processes of decision making has occurred across the health-care sector.…”
Section: Public Involvement In Biobanksmentioning
confidence: 99%
“…6 Public involvement is seen as a means to produce and maintain public trust and legitimacy, which are essential for the functioning of biobanks. 6 This increase in efforts to involve the public in processes of decision making has occurred across the health-care sector. In the UK, 'public involvement' is mandated by the National Institute for Health Research and other research funders.…”
Section: Public Involvement In Biobanksmentioning
confidence: 99%
“…A recent systematic review by Nunn, Tiller, Fransquet, and Lacaze [2019] evaluated public involvement in human genomics research projects worldwide. They found that only about 30% of the initiatives described public involvement in any capacity, and 2% involved public beyond data collection and at the level of co‐creation of the scientific process, so called “citizen science.” Clearly, there is a great need to increase public involvement in genetics research, and develop standardized methods of reporting their engagement; the impact of such involvement may be evaluated by assessing both qualitative and quantitative data [Nunn et al, 2019]. A series of guidelines have recently been developed by the National Institute of Mental Health workgroups (http://nimh.nih.gov), particularly, in relation to methodological aspects of genetics research studies, but they did not include any recommendation for incorporating patient perspectives in study design.…”
Section: Introductionmentioning
confidence: 99%